Development and assessment of a novel air/water hybrid cooling system coupling two units for energy and water saving. (August 2022) - Wang, Jinshi; Xue, Kai; Zhang, Guilong; Chen, Weixiong; Li, Gen; Zhang, Juntai; Zhang, Guozhu
Highlights: An air/water hybrid cooling system is designed and assessed. The proposal applies to the thermal power plants with both water-cooling units and indirect air-cooling units. The optimal operation strategy is proposed for energy saving in summer and water saving in winter. The coal consumption rate can be reduced by 1.43 g/kWh for the case units. Abstract: For the purpose of reducing coal consumption, decreasing CO2 emissions, and improving the economic interests of thermal power plants, a novel air/water hybrid cooling system coupling two units has been developed and assessed. The hybridization is achieved by the heat exchange of the circulating cooling water from two units, which is appropriate for the power plants with both water-cooling units and indirect air-cooling units, such as in North China region. Two schemes with different circulating water returning positions were compared on basis of thermodynamic and economic evaluation. Finally, the scheme that cooled circulating water was introduced to the air-cooling tower outlet was considered as the optimal design, which has a coal saving rate of 1.43 g/kWh at the design condition, with a 3.59-year payback period. In addition, this work focused on operation strategies to obtain optimum operation range, contributing to less coal consumption in summer and less water consumption in winter. The results indicate that annual coal consumption can be reduced by about 1400 tons in the reference power plant, the CO2 emission is decreased by 3490 tons, and 50, 000 tons of water could be saved. This technology is expected to be further promoted to practical engineering for sustainable development.